Dominant LMAN2L mutation causes intellectual disability with remitting epilepsy. Issue 4 (7th March 2019) - Alkhater, Reem A.; Wang, Peixiang; Ruggieri, Alessandra; Israelian, Lori; Walker, Susan; Scherer, Stephen W.; Smith, Mary Lou; Minassian, Berge A.
Abstract: Mis‐secreted glycoproteins (LGI1, reelin) are emerging causes of epilepsy. LMAN2L belongs to a glycoprotein secretion chaperone family. One recessive LMAN2L missense mutation predicted to impair the chaperone's interaction with glycoproteins was reported in a family with intellectual disability (ID) and remitting epilepsy. We describe four members of a family with autosomal dominant inheritance of a similar phenotype. We show that they segregate a NM_001142292.1:c.1073delT mutation that eliminates LMAN2L's endoplasmic reticulum retention signal and mislocalizes the protein from that compartment to the plasma membrane. LMAN2L mislocalization, like impaired glycoprotein interaction, disturbs brain development, including generation of developmentally restricted epilepsy.